Pseudomorphic replacement of single calcium carbonate crystals by polycrystalline apatite - Kasioptas, A.; Perdikouri, C.; Putnis, Christine; Putnis, Andrew (2008)
During chemical weathering and natural hydrothermal reactions, apatite can form by replacing calcium carbonates. In hydrothermal experiments in which aragonite and calcite single crystals have been reacted with phosphate solutions, the carbonates are replaced by polycrystalline hydroxylapatite (HAP). In both cases the crystals have retained their overall morphology while their compositions have changed significantly. The HAP appears to have a crystallographic relationship to the parent carbonate crystals. The textural relationships are consistent with an interface-coupled dissolution-precipitation mechanism. Structural relationships and relative molar volumes and solubilities appear to be factors that greatly affect replacement reactions. © 2008 The Mineralogical Society.